Pengaruh Budaya Adhokrasi dan Kompensasi terhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel Mediasi - Amrullah, Afifuddin; Soelistya, Djoko (Gapenas Publisher, 2025)
This study aims to analyze the effect of adhocracy culture and compensation on employee performance, with work motivation as a mediating variable at PT Adiprima Suraprinta. The study is motivated by the phenomenon of declining employee performance during the 2020–2024 period, despite questionnaire results indicating relatively high perceived performance. A quantitative research approach was employed. The population consisted of all employees of PT Adiprima Suraprinta, with 334 permanent employees selected using purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that adhocracy culture and compensation have a positive and significant effect on work motivation and employee performance. Furthermore, work motivation partially mediates the relationship between adhocracy culture and compensation on employee performance. These findings emphasize that strengthening an innovative organizational culture and implementing an appropriate compensation system can enhance work motivation, which in turn contributes to sustainable improvements in employee performance